STRENGTHENING THE AUTHORITY OF LAPS SJK IN RESOLVING DIGITAL TRANSACTION DISPUTES IN INDONESIA - Adhitya Mizar Pranata; Sukarmi; Reka Dewantara (KANUN:JURNAL ILMU HUKUM, 2025)
Digitalization in Indonesia’s banking sector has significantly transformed financial transaction mechanisms, particularly through the growing reliance on digital services. While this development expands access to financial products, it concurrently increases the likelihood of disputes involving customers, banks, and third-party providers. This study examines the effectiveness of Alternative Dispute Resolution (ADR), particularly the Alternative Dispute Resolution Institution for the Financial Services Sector (LAPS SJK), in addressing digital transaction disputes in Indonesia’s banking industry. Employing a normative juridical approach grounded in the relevant regulatory framework, this research demonstrates that ADR through LAPS offers substantial advantages as a fast, efficient, and relatively low-cost dispute resolution mechanism compared to litigation. Nevertheless, its implementation remains constrained by limited public awareness, misaligned consumer expectations, and the restricted authority of LAPS in ensuring compliance with its decisions. The study underscores the urgency of strengthening the regulatory framework to expand the authority of LAPS, including the imposition of sanctions on non-compliant parties and the comprehensive handling of consumer complaints arising from digital financial transactions.